LncRNA GAS5 Knockdown Mitigates Hepatic Lipid Accumulation via Regulating MiR-26a-5p/PDE4B to Activate cAMP/CREB Pathway - Xu, Shizan; Wang, Yajie; Li, Zhengyang; Hua, Qian; Jiang, Miao; Fan, Xiaoming (Frontiers in Endocrinology, 2022)
Objective: Non-alcoholic liver disease (NAFLD) can be attributed to the dysregulation of hepatic lipid metabolism; however, its cellular and molecular mechanisms remain unclear. This study aims to explore the effect of long non-coding RNA growth arrest specific 5 (GAS5) on hepatic lipid metabolism in NAFLD. Methods: Obese mice, high fat diet-fed mice and free fatty acid-stimulated cells were used for GAS5 expression detection. GAS5 overexpression or knockdown models were established to elucidate the regulatory function of GAS5 in de novo lipogenesis (DNL) and mitochondrial function. Bioinformatic analyses and dual luciferase assays were used to investigate the interaction between GAS5, miR-26a-5p and phosphodiesterase (PDE) 4B. The involvement of the cyclic adenosine monophosphate (cAMP)/cAMP-response element-binding protein (CREB) pathway was evaluated using H89 and forskolin treatment. Results: GAS5 was activated in vitro and in vivo NAFLD models. Knockdown of GAS5 reduced lipid droplet accumulation, DNL associated enzymes and preserved mitochondrial function, while GAS5 overexpression exacerbated hepatic lipid accumulation. Mechanistically, GAS5 sponged miR-26a-5p to increase PDE4B expression and subsequently modulated DNL and mitochondrial function via the cAMP/CREB pathway. Conclusion: Therefore, downregulation of GAS5 mitigates hepatic lipid accumulation through miR-26a-5p/PDE4B axis, which correlates with the cAMP/CREB pathway.